Predictors of Treatment Failure for Hip and Knee Prosthetic Joint Infections in the Setting of 1- and 2-Stage Exchange Arthroplasty: A Multicenter Retrospective Cohort. (21st October 2019) - Kandel, Christopher E; Jenkinson, Richard; Daneman, Nick; Backstein, David; Hansen, Bettina E; Muller, Matthew P; Katz, Kevin C; Widdifield, Jessica; Bogoch, Earl; Ward, Sarah; Sajja, Abhilash; Jeldes, Felipe Garcia; et al.
Abstract: Background: Prosthetic hip and knee joint infections (PJIs) are challenging to eradicate despite prosthesis removal and antibiotic therapy. There is a need to understand risk factors for PJI treatment failure in the setting of prosthesis removal. Methods: A retrospective cohort of individuals who underwent prosthesis removal for a PJI at 5 hospitals in Toronto, Canada, from 2010 to 2014 was created. Treatment failure was defined as recurrent PJI, amputation, death, or chronic antibiotic suppression. Potential risk factors for treatment failure were abstracted by chart review and assessed using a Cox proportional hazards model. Results: A total of 533 individuals with prosthesis removal were followed for a median (interquartile range) of 814 (235–1530) days. A 1-stage exchange was performed in 19% (103/533), whereas a 2-stage procedure was completed in 88% (377/430). Treatment failure occurred in 24.8% (132/533) at 2 years; 53% (56/105) of recurrent PJIs were caused by a different bacterial species. At 4 years, treatment failure occurred in 36% of 1-stage and 32% of 2-stage procedures ( P = .06). Characteristics associated with treatment failure included liver disease (adjusted hazard ratio [aHR], 3.12; 95% confidence interval [CI], 2.09–4.66), the presence of a sinus tract (aHR, 1.53; 95% CI, 1.12–2.10), preceding debridement with prosthesis retention (aHR, 1.68; 95% CI, 1.13–2.51), a 1-stage procedure (aHR, 1.72; 95% CI, 1.28–2.32), and infection due to Gram-negative bacilli (aHR, 1.35; 95% CI, 1.04–1.76). Conclusions: Failure of PJI therapy is common, and risk factors are not easily modified. Improvements in treatment paradigms are needed, along with efforts to reduce orthopedic surgical site infections. Abstract : Prosthetic joint infections are challenging to eradicate and in this retrospective cohort the characteristics associated with treatment failure included liver disease, presence of a sinus tract, prior debridement with prosthesis retention, a one-stage procedure, and infection with a Gram-negative bacilli.